Two-Phase Approach to International Logistics Hub Location: The Case of Yangtze River Delta - Zhang, Xinfang; Liu, Chengliang; Peng, Yan (IEEE transactions on engineering management, 2024)
An international logistics hub (ILH) is an important component of the modern integrated logistics system, and its location selection has always been a hot topic in logistics management. In this article, we aim in developing a two-phase location framework to determine the most preferred ILHs in the logistics network. First, a revised fuzzy C-means clustering algorithm is proposed to identify candidate ILHs from the perspective of microlevel evaluation. The evaluation index system is constructed by the proposed index screening model. Second, an adaptive gravity p -median model is established to determine optimal ILHs and freight flow allocations from a macroplanning perspective. The optimization model takes into account the attractiveness of nodes, the distribution of logistics demand, and the total transportation cost between nodes in the network. Finally, the two-phase approach is applied to the location of ILHs in the Yangtze River Delta (YRD), China. Results show that five alternative locations are identified from 27 cities, and four optimal ILHs (Shanghai, Suzhou, Hangzhou, Ningbo) are determined from five candidate ILHs. The freight flow distribution shows that the share transshipped through them is 33.05%, 26.81%, 22.59%, and 17.55%, respectively. Furthermore, the optimized hub location in the case study is consistent with the practice situation in the YRD. These results illustrate the applicability and feasibility of the proposed two-phase approach for the logistics hub location. We also provide insights for planning logistics hubs and optimizing transportation networks in the YRD from the perspectives of megalopolis and national levels.